2022
DOI: 10.1111/bjh.18293
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin modulates CD4+ T‐cell differentiation via metabolic reprogramming in immune thrombocytopenia

Abstract: Summary Immune thrombocytopenia (ITP) is an acquired autoimmune disease, in which the imbalance of CD4+ T cell subsets play a key role in the pathogenesis. Since T cells highly depend on metabolism for their function, we hypothesized that T cell dysfunction may be due to intracellular metabolic reprogramming. We found that in ITP, T cell metabolism shifts from oxidative phosphorylation to glycolysis. Empagliflozin, a sodium–glucose cotransporter 2 inhibitor, has shown regulatory metabolic effects on proximal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Treg cells, which were responsible for immune tolerance, have been studied the most during a long period, and these cells were deficient in ITP and failed to suppress the excessive auto-reactive T cells ( 43 , 44 ). Furthermore, the imbalance of Th cells has been evidenced by an increasing polarization of Th1 and Th17 cells, as well as their cytokines ( 45 ). Increased Th17 cells and related cytokines have been evidenced in ITP patients and mice and correlated with the course of the disease and response to treatment ( 46 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Treg cells, which were responsible for immune tolerance, have been studied the most during a long period, and these cells were deficient in ITP and failed to suppress the excessive auto-reactive T cells ( 43 , 44 ). Furthermore, the imbalance of Th cells has been evidenced by an increasing polarization of Th1 and Th17 cells, as well as their cytokines ( 45 ). Increased Th17 cells and related cytokines have been evidenced in ITP patients and mice and correlated with the course of the disease and response to treatment ( 46 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…The latest research shows that HK2 regulates microglial functions by upregulating glycolytic flux and maintaining mitochondrial activity [47,48]. Furthermore, recent studies have shown that SGLT2i can modulate the polarization phenotype of peripheral immune cells by regulating glucose metabolic reprogramming by inhibiting mTOR signaling [49]. Aerobic glycolysis, phosphorylated mTOR, and HK2 expression are increased by proinflammatory microglia [44].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have unveiled the impact of SGLT2 inhibitors on T cell effector function and differentiation via metabolic reprograming. 12 , 60 A recent study by Jenkins et al. demonstrated that in vitro exposure to canagliflozin inhibits T cell receptor signaling, leading to compromised ERK and mTORC1 activity in T cells.…”
Section: Immunomodulatory Mechanism Of Sglt2 Inhibitors and Its Impac...mentioning
confidence: 99%
“…Another in vitro experiment involving T cells isolated from immune thrombocytopenia patients revealed that empagliflozin increased the regulatory T cell subset while decreasing the Th1 and Th17 T cell subsets. 60 This effect was counteracted by the use of an mTOR agonist. This study suggests that SGLT2 inhibitors may modulate the metabolic reprogramming of CD4 T cells through the mTOR signaling pathway.…”
Section: Immunomodulatory Mechanism Of Sglt2 Inhibitors and Its Impac...mentioning
confidence: 99%